2019
DOI: 10.1007/s13593-019-0577-z
|View full text |Cite
|
Sign up to set email alerts
|

Artificial selection of insects to bioconvert pre-consumer organic wastes. A review

Abstract: As the human population continues to grow, so too do the concerns regarding the sustainability of waste management from our food production systems. Faced with limited environmental resources for food production, issues related to food loss and waste are critical in mitigating challenges stemming from projected population growth and long-term food security and sustainability. The potential for using insects to consume organic waste materials and convert them into feed for animal, biofuels, and other valuable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 109 publications
0
16
0
Order By: Relevance
“…This type of selection varies based on the nutritional requirement of each species and maintains the balance of digestible carbohydrates and proteins ( Behmer 2009 , Morales-Ramos et al 2011 ), lipids and vitamins ( Schiff et al 1988 ). Self-selection can also occur according to the stage of the insect ( Deans et al 2017 , Fowles and Nansen 2019 ). In this study, we observed that T. molitor larvae sought to consume the ideal proportion of the mixture of the control diet with the poultry litter for their nutritional balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of selection varies based on the nutritional requirement of each species and maintains the balance of digestible carbohydrates and proteins ( Behmer 2009 , Morales-Ramos et al 2011 ), lipids and vitamins ( Schiff et al 1988 ). Self-selection can also occur according to the stage of the insect ( Deans et al 2017 , Fowles and Nansen 2019 ). In this study, we observed that T. molitor larvae sought to consume the ideal proportion of the mixture of the control diet with the poultry litter for their nutritional balance.…”
Section: Discussionmentioning
confidence: 99%
“…We know that insects are great recyclers of byproducts, Fowles and Nansen (2019) showed a review, about research on the growth performance and feeding conversion of these species, suggesting they alone are not sufficient to fully capitalize on the high diversity of unique organic wastes available for bioconversion.…”
Section: Discussionmentioning
confidence: 99%
“…Eight years selection in yellow mealworm led to increases of pupal size, growth rate, fecundity and feed conversion rates compared to the ancestral stain, although survival was lower (Morales-Ramos et al, 2019). Also, it may be possible to select lines of black soldier fly which could handle certain types of organic side-streams (Fowles and Nansen, 2019).…”
Section: Industrial Productionmentioning
confidence: 99%
“…Urban agriculture may be another solution; however, in this case, additional studies are needed for a more complete assessment [45]. Farming fish is another possibility to achieve more sustainable food security [46], as are the home food gardens [47], revitalising local food systems [48], using insects as bioconverters of organic waste [49], obtaining protein from food waste [50], food forestry [51], natural food [52], better governance and conception [53], hydroponic farm [54], organic farming [55], crops resilience assessments [56], wild edible greens [57], food loss, and waste management [58].…”
Section: Literature Surveymentioning
confidence: 99%